Estudo da clarificação de água de açude por eletrocoagulação/flotação e reúso do lodo gerado na remoção de íons metálicos - Maia, Fábio Erlan Feitosa (2016)
The water crisis in the state of Ceará, located in the northeastern region of Brazil, reached the third consecutive year in 2016 with COGERH fluviometric data that showed that more than 90% of the state's hydrographic basins were with less than 30% of their maximum water reserve capacities. FUNCEME's rain forecasts indicated scarce amounts of rain for the next years (2017, 2018 and 2019) while the water and sewage company of the state of Ceará (CAGECE) highlighted the need for a contingency plan involving dams in the city of Fortaleza which could be used as an alternative measure in public supply. As a consequence, alternative water collection and treatment methods are extremely necessary to make it possible to supply populations in areas impacted by water scarcity. Thus, the water from the Santo Anastácio reservoir, which is located inside the Federal University of Ceará, could eventually also be used as a water resource in Fortaleza, after an adequate treatment that would ensure the drinking standards required by the Brazilian standard. This work proposes to study the application of the electrocoagulation / flotation process, an advanced oxidative process (POA), to clarify the waters of the Santo Anastácio weir (ASA) as well as to use the generated sludge containing microalgae during the electrocoagulation / flotation process as an alternative method for removal of toxic ions. The electrocoagulation / flotation process involved the use of pulsed direct current using aluminum electrodes connected in series. The samples with high turbidity (1.5 NTU) generated about 8g of dry biomass for every 60L of treated water. The flotated sludge was separated, dried and later used as an adsorbent to remove copper ions in aqueous solutions with concentrations ranging from 5.0 mg.L-1 to 400 mg.L-1. Batch adsorption studies were performed using the Langmuir and Freundlich isotherms as adsorptive models. The sludge adsorption capacity was 18.5 mg.g-1 while the time to remove 50% copper occurred in the initial 10 min. The characterization of dry sludge was carried out by the analysis of pHpzc surface load, X-ray fluorescence and infrared.